Mid-term to long-term outcome and risk factors for failure of 158 hips with two-stage revision for periprosthetic hip joint infection - M. Abuelnour; C. McNamee; A. B. Rafi; W. Hohlbein; W. Hohlbein; P. Keogh; J. Cashman (Journal of Bone and Joint Infection)
Introduction: This study aimed to evaluate infection-free survival and outcomes after two-stage revision surgery for hip periprosthetic joint infection (PJI) performed in a specialised arthroplasty unit over 20 years. Methods: We retrospectively identified 158 hips (154 patients) treated with two-stage revision surgery for hip PJI between 2001 and 2021. We analysed their data and presented their infection-free survival, re-operation rate, mortality, risk factors and complications. Results: The mean follow-up time was 9 (2 to 21.7) years. A total of 22 hips (13.9 %) were re-infected. The infection-free survival was 94.4 % at 2 years, 89.3 % at 5 years, 84.2 % at 10 years, and 82.6 % at 15 and 20 years. The re-operation rate for aseptic causes was 12 %, and the most common cause of re-operation was dislocation (7 %). The cumulative survival for re-operation for aseptic causes was 93.6 % at 2 years, 89.7 % at 5 years, 88.8 % at 10 years, and 82.8 % at 15 and 20 years. The cumulative survival for all-cause re-revision was 88.8 % at 2 years, 80.8 % at 5 years, 74.9 % at 10 years, and 68 % at 15 and 20 years. The mean Western Ontario and McMaster Universities Arthritis Index (WOMAC) hip score significantly improved from 68.3 at the pre-operative stage to 35.9 at 2.1 (2 to 3.3) years, 35.3 at 5.3 (5 to 8.4) years, 38.3 at 11.3 (10–15) years and 43.8 at 18.7 (16.5 to 21.7) years (p<0.01). Duration of antibiotics and gram-negative infection were the only predictive risk factors for re-infection. Conclusion: Our results of the two-stage revision protocol for hip PJI were satisfactory and comparable with the best reported outcomes.